Epidemiological aspects of the persistent transmission of rabies during an outbreak (2010 – 2017) in Harare, Zimbabwe - Coetzer, Andre; Gwenhure, Lambert; Makaya, Pious; Markotter, Wanda; Nel, Louis (PloS one, 2019)
Canine-mediated human rabies is endemic to the entire African continent, where the disease burden is often highest in rural communities of resource-limited countries. In this study, we analysed an animal rabies outbreak, which had persisted since 2010 in the predominantly metropolitan capital city of Zimbabwe, Harare. As rabies is considered to disproportionally affect rural communities, the persistence of urban rabies in this metropolitan setting is of interest. In order to gain an improved understanding of the epidemiology of the outbreak under investigation, we utilised both routine surveillance data that had been collected during the first eight years of the outbreak (2010-2017), as well as molecular epidemiological analyses relying on the Bayesian Markov Chain Monte Carlo methodology. This approach allowed us to characterize virus transmission by identifying specific suburbs within the city limits where persistent disease transmission took place, while also confirming that immunologically naïve dogs were the most likely reservoir species in and around the city. In addition to gaining an improved local understanding of the outbreak, we are also able to infer that rabies was likely introduced to the city in 2010 when a rabid animal was moved from the north-east of Zimbabwe into Harare-resulting in an epizootic event. The work presented here not only showcased the value of combining conventional and molecular epidemiological data, but also highlighted the importance of maintaining rabies vaccination coverage and continued public awareness in urban areas where the risk appears to be low. By educating the general population on rabies and relying on owners to bring their companion animals to strategically placed vaccination points, the control and elimination of rabies from Harare may be feasible.